Pathological complete response of locally advanced colon cancer after preoperative radiotherapy: a case report and narrative review of the literature - Sho Sekiya; Kiyotaka Imamura; Shintaro Takeuchi; Koichi Teramura; Yusuke Watanabe; Eiji Tamoto; Minoru Takada; Yoshihiro Kinoshita; Yoshiyasu Anbo; Fumitaka Nakamura; Nobuichi Kashimura; Hiroko Noguchi; et al. (Surgical Case Reports)
Abstract Background The oncological effectiveness of preoperative radiotherapy for locally advanced colon cancer is unclear. We report a case of pathological complete response in a patient with locally advanced ascending colon cancer after preoperative radiotherapy following failure of chemotherapy. Case presentation A 65-year-old Japanese woman presented with malaise and hematochezia. A computed tomography (CT) revealed a tumor in the ascending colon which seemed to infiltrate the adjacent structures. She was diagnosed with locally advanced ascending colon cancer stages T4b, N2a, M0, and IIIC. We selected modified FOLFOX6 with panitumumab as neoadjuvant chemotherapy. However, we discontinued the chemotherapy after the 8th cycle because of disease progression and severe adverse effects. The patient then underwent radiotherapy of 60 Gy in 30 fractions, resulting in significant tumor size reduction. One month after the radiotherapy, we performed a right hemicolectomy with multivisceral resection without complications. Histopathologically, we found no residual cancer cells in the resected specimen. The patient remains alive and has not required additional therapies for 24 months, as there are no signs of recurrence. Conclusions The present case suggests that preoperative radiotherapy might be an effective treatment options for locally advanced colon cancer.